دور المنظمات غير الحكومية في التربية من أجل التنمية المستدامة "دراسة ميدانية للمنظمات غير الحكومية في محافظة اللاذقية" (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
ركز البحث على مفهوم التربية من أجل التنمية المستدامة، ودور المنظمات غير الحكومية في تحقيقها، كونها عنصراً فاعلاً في دفع جهود عملية التنمية الشاملة، وهدف البحث إلى معرفة مدى تحقيق أهداف التربية من أجل التنمية المستدامة في برامج المنظمات غير الحكومية في محافظة اللاذقية، ولتحقيق هدف البحث قامت الباحثة  بتصميم استبانة تضمنت(34)عبارة موجهة للمستفيدين، وهي مؤلفة من أبعاد التنمية المستدامة الثلاث(الاقتصادية، الاجتماعية، البيئية)، وكل بعد تضمن مجالين(التوعية والتعليم، التأهيل والتدريب)، وتم التأكد من صدقها وثباتها ومن ثم تطبيقها على عينة مؤلفة من(150) مستفيداً ومستفيدة، وشملت عينة البحث ثلاث منظمات من المنظمات غير الحكومية في اللاذقية، و قد أظهرت نتائج البحث وجود فروق ذات دلالة إحصائية عند مستوى الدلالة(0,05) بين متوسط درجات المستفيدين من المنظمات غير الحكومية تبعاً لمتغير(المنظمة والتحصيل العلمي)، وتبين عدم وجود فروق ذات دلالة إحصائية بين متوسط درجات المستفيدين بالنسبة لمتغير العمر، وخلص البحث إلى وجود فروق ذات دلالة إحصائية بين متوسط إجابات المستفيدين في أبعاد التنمية المستدامة(الاقتصادية، الاجتماعية) تبعاً للمجالات التربوية للتنمية المستدامة(التوعية والتعليم، التأهيل والتدريب). كما توصل إلى أنه لا يوجد فروق ذات دلالة إحصائية بين متوسط إجابات المستفيدين في البعد البيئي للتنمية المستدامة تبعاً للمجالات التربوية (التوعية والتعليم، والتأهيل والتدريب). ويؤكد البحث أن المنظمات غير الحكومية تحقق بعض الحاجات التربوية للمستفيدين, منها: مجال التوعية والتعليم و التدريب والتأهيل، لتحقيق أهداف التنمية المستدامة، و أبرز هذا البحث دور التربية في تحقيق أهداف التنمية المستدامة من خلال برامج المنظمات السورية غير الحكومية التي تهتم بمجالات التوعية والتعليم، والتأهيل والتدريب للمستفيدين. Being an essential factor in advancing the comprehensive development process, one goal this research focuses on the concept of Education for sustainable development and the role of Non-Governmental Organizations (NGOs) in achieving it. The other goal of research is to investigate the extent to which these objectives of education for sustainable development are realized in the programs of Non-Governmental Organizations in Lattakia. To achieve the goals of this research, the researcher designs a questionnaire composed of 34 items addressed to NGO beneficiaries. These items have the three dimensions of sustainable development (economic, social, and environmental), and each dimension contains two components (awareness and education, rehabilitation and training). Questionnaires are checked for consistency and reliability, then applied to a sample composed of 150 NGO beneficiaries (male or female). Also, this sample includes three NGOs from Lattakia. The results obtained show significant differences (P =0.05) between the average scores of NGO beneficiaries for  the two variables, NGOs and educational attainment. However,  no significant differences are detected between NGO beneficiaries' average scores for the age variable. This research concludes that there are significant differences between the average response of NGO beneficiaries in the sustainable development dimensions (economic, social), depending on the areas of education for sustainable development (awareness and education, rehabilitation, and training). We have also found that there are no significant differences between beneficiaries' average responses in the environmental dimension of sustainable development according to the areas of education (awareness and education, rehabilitation and training). This research ascertains that NGOs provide some educational needs for beneficiaries such as awareness and education, training and rehabilitation, for achieving sustainable development objectives. Also, this research points out the role of education in achieving sustainable development goals through the programs of Syrian NGOs concerned with beneficiaries' education, rehabilitation, and training.